Access to Credit, Technological Innovation and Global Integration of Argentine Companies 2010-2012 (2019)
Based on data from ENDEI (2010-2012) this paper analyzes credit constraints that Argentine companies face to implement innovative activities. The evidence shows that constraints are tighter for SMB compared to big companies. Using OLS we also estimate differentials in investments on innovation between firms that have access to credits to finance their innovation compared to those that are constrained. We find that, after controlling for different characteristics, firms that are not constrained invest 30,74% more in innovation, on average, than constrained firms. This difference is decrescent with the size of the companies. Finally, using a linear probability model we evaluate the relation between credit access and the likelihood of global integration of Argentine companies. Our findings indicate that having access to credit for investing on innovative activities is related with a higher probability of exporting, which is consistent with theoretical developments that point to the existence of a complementarity between innovative investments and the export ability.